1997
DOI: 10.1073/pnas.94.26.14596
|View full text |Cite
|
Sign up to set email alerts
|

The restriction–modification genes of Escherichia coli K-12 may not be selfish: They do not resist loss and are readily replaced by alleles conferring different specificities

Abstract: Type II restriction and modification (R-M) genes have been described as selfish because they have been shown to impose selection for the maintenance of the plasmid that encodes them. In our experiments, the type I R-M system EcoKI does not behave in the same way. The genes specifying EcoKI are, however, normally residents of the chromosome and therefore our analyses were extended to monitor the deletion of chromosomal genes rather than loss of plasmid vector. If EcoKI were to behave in the same way as the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Host cell killing was also shown with the type IV enzyme McrBC by the introduction of a DNA methylation gene (96). Although such selfish behavior appears to be a widespread phenomenon with type II R-M systems, it is not common in type I or III enzymes (97). In the latter systems, the MTase and the REase are subunits of the same protein complex, and the intracellular ratios of MTase to REase do not change over time upon the loss of the R-M locus, a prerequisite for function as an addiction module.…”
Section: Additional Functions Of R-m Systems Selfish Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Host cell killing was also shown with the type IV enzyme McrBC by the introduction of a DNA methylation gene (96). Although such selfish behavior appears to be a widespread phenomenon with type II R-M systems, it is not common in type I or III enzymes (97). In the latter systems, the MTase and the REase are subunits of the same protein complex, and the intracellular ratios of MTase to REase do not change over time upon the loss of the R-M locus, a prerequisite for function as an addiction module.…”
Section: Additional Functions Of R-m Systems Selfish Genesmentioning
confidence: 99%
“…In the latter systems, the MTase and the REase are subunits of the same protein complex, and the intracellular ratios of MTase to REase do not change over time upon the loss of the R-M locus, a prerequisite for function as an addiction module. Studies of EcoKI, one of the earliest-characterized type I enzymes, revealed that the enzyme does not behave as a selfish element (97). Similarly, EcoR124I, another well-studied type IC enzyme encoded on a large plasmid, does not seem to exhibit postsegregational killing (98).…”
Section: Additional Functions Of R-m Systems Selfish Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the bacterial chromosome becomes susceptible to restriction as cell growth dilutes the modification enzyme (Handa et al, 2000). However, while the loss of genes that specify some simple R-M systems leads to cell death, the loss of genes that specify other, more complex, R-M systems causes no detectable viability problem (O'Neill et al, 1997 ;Kulik & Bickle, 1996 ;Makovets et al, 1998). In this by EcoKI and thus forms plaques with reduced efficiency (e.o.p.…”
Section: Background and Aimsmentioning
confidence: 99%
“…However, the level of such killing varies among RM systems, presumably reflecting the complexity of the parasite-host interaction (and we will analyze one example in the present work). Postsegregational killing has not been proven for type I RM systems examined so far (34,53). Host attack by EcoKI, one of these type I restriction enzymes tested, is prevented by its proteolytic cleavage (11).…”
mentioning
confidence: 97%